High morbidity and mortality associated with primary bloodstream infections among pediatric patients with cancer at a Guatemalan tertiary referral hospital - Mukkada, Sheena; Melgar, Mario; Bullington, Craig; Chang, Alicia; Homsi, Maysam R.; Gonzalez, Miriam L.; Antillon, Federico; Su, Yin; Tang, Li; Caniza, Miguela A. (Frontiers in Public Health, 2022)
Infectious complications remain major contributors to adverse outcomes in patients treated for non-communicable disease, particularly in resource limited settings. We performed a 5-year retrospective study of primary bloodstream infections at a dedicated pediatric oncology center in Guatemala. Two hundred and twelve episodes occurring in 194 unique patients qualified for inclusion. Patients required intensive care unit admission in 55% of episodes and death occurred in 24% of episodes. Despite subspecialty support in infectious diseases, poor outcomes, including prolonged hospitalization and mortality, were frequent. Our findings suggest that investments in laboratory and clinical data collection are critical to understanding the contributors to poor outcomes and therefore to improving the quality of bloodstream infection management in resource limited settings.